Upper Gastrointestinal Tract IrAEs: A Case Report About Sintilimab-Induced Acute Erosive Hemorrhagic Gastritis - Ai, Qi; Chen, Wen; Li, Yonggui; Li, Guoqing (Frontiers in Immunology, 2022)
Introduction: Immune checkpoint inhibitors (ICIs) have now become the standard therapy for malignancies like non-small cell lung cancer and classical Hodgkin lymphoma. ICIs are associated with unique immune-related adverse events (irAEs) caused by dysregulated immune activation. Treatment of lower gastrointestinal (GI) tract irAEs, such as colitis, is more common. However, for upper gastrointestinal tract irAEs, there is a lack of consensus in terms of globally standardized disease classification and treatment guidelines. Herein, we report a case of sintilimab-induced acute erosive hemorrhagic gastritis. Case presentation: A 54-year-old man with metastatic NSCLC (PT2N2M1 stage IV) underwent treatment with eight courses of sintilimab + bevacizumab, followed by maintenance therapy with sintilimab alone. However, he presented with epigastric pain and melena at the end of the first sintilimab treatment, and the symptoms occurred repeatedly after regular treatment with acute erosive hemorrhagic gastritis. Repeat esophagogastroduodenoscopy (EGD) showed severe hemorrhagic gastritis; symptomatic relief and improvement in EGD images were noted for as long as he was being treated with steroids methylprednisolone sodium. Conclusion: To our knowledge, we herein describe the first case of sintilimab-associated acute erosive hemorrhagic gastritis, an upper gastrointestinal toxicity event. Throughout the treatment progression, differential diagnosis, multidisciplinary discussion, and the use of immunosuppressants were instrumental in clarifying the diagnosis and were crucial to the patient's prognosis and continued treatment with ICIs. Keywords: Sintilimab, Immune checkpoint inhibitor, acute erosive hemorrhagic gastritis, Immune-related adverse event, Upper gastrointestinal tract irAE